Dual beam swept source optical coherence tomography for microfluidic velocity measurements - Rigas, Evangelos (Cranfield University, 2018)
Microfluidic flows are an increasing area of interest used for “lab-on-a-chip” bioanalytical techniques, drug discovery, and chemical processing. This requires optical, non-invasive flow-visualization techniques for characterising microfluidic flows. Optical Coherence Tomography (OCT) systems can provide three-dimensional imaging through reasonably-opaque materials with micrometre resolution, coupled to a single optical axis point using optical fibre cables. Developed for imaging the human eye, OCT has been used for the detection of skin cancers and endoscopically in the human body. Industrial applications are growing in popularity including for the monitoring of bond-curing in aerospace, for production-line non-destructive-testing, and for medical device manufacturing and drug encapsulation monitoring. A dual beam Optical Coherence Tomography system has been developed capable of simultaneously imaging microfluidic channel structures, and tracking particles seeded into the flow to measure high velocity flows, using only a single optical access point. This is achieved via a dual optical fibre bundle for light delivery to the sample and a custom high-speed dual channel OCT instrument using an akinetic sweep wavelength laser. The system has 10 μm resolution in air and a sweeping rate of 96 kHz. This OCT system was used to monitor microfluidic flows in 800 μm deep test chips and Poiseuille flows were observed.